Faktor-Faktor Yang Mempengaruhi Keputusan Pembelian Aksesoris Handphone Merk Iphone - Halim, firmansyah; Rizal, Nur (P3M STIEM, 2021)
This study aims to determine whether trust has an effect on purchasing decisions, price affects purchasing decisions, advertising affects purchasing decisions and the effect of trust, price and advertising simultaneously on purchasing decisions.Data collection uses primary data obtained from STIEM Bongaya students who use iPhone cellphone accessories which are then used as respondents using incidental sampling techniques where the distribution of the questionnaire is by chance or who is met so that the researchers set a sample of 50 respondents. The results of primary data collected through the distribution of the questionnaire have been tested using classical assumption tests in the form of normality assumptions, multicollinearity assumptions and heteroscedasticity assumptions. Methods of data analysis using descriptive statistical analysis techniques and inferential statistical analysis. The outcomes showed that first, trust has a positive and critical impact on buying choices. The two costs